Cardiovascular Risk Factor Status in Hospitalized Patients With Type 2 Diabetes in China - Yang, Xiaoyun; Liu, Qian; Fan, Yuxin; Ding, Li; Wang, Ruodan; Hu, Gang; Liu, Ming (Frontiers in Endocrinology, 2021)
Background: Controlling blood glucose, blood pressure, and blood lipid is of great importance for patients with type 2 diabetes, not only for cardiovascular disease, but also for other complications. Previous studies mainly focused on the control rate of outpatients and the results were suboptimal, but few studies aimed at the inpatients. Method: The present study involved 3245 hospitalized patients with type 2 diabetes from 2013 to 2017 in the Department of Endocrinology and Metabolism of Tianjin Medical University General Hospital. The percentages of inpatients’ attainment of the China Diabetes Society and the American Diabetes Association goals were calculated for major cardiovascular risk factors (HbA1c, blood pressure and blood lipid). The prevalence of the microvascular and macrovascular complications was also assessed. Result: According to the Chinese Diabetes Society goals, the percentages of patients met HbA1c <7%, blood pressure <130/80 mmHg, normal lipids, and all three goals were 26.7%, 14.8%, 10.4% and 0.2% in 2013, and 30.5%, 16.2%, 8.0%, and 0.9% in 2017, respectively. The percentage of patients who met all three American Diabetes Association goals (HbA1c<7%, blood pressure <140/90 mmHg, low-density lipoprotein cholesterol <2.6 mmol/L) increased from 4.3% in 2013 to 9.0% in 2017. The prevalence of major diabetes complications including coronary heart disease (31.7% vs. 31.9%), stroke (16.7% vs 14.8%), diabetic kidney disease (37.9% vs. 35.8%), diabetic retinopathy (48.0% vs. 46.5%), neuropathy (63.1% vs 61.9%), and diabetic foot (0.8% vs. 1.2%) were stable from 2013 to 2017. Conclusion: During 2013 to 2017, control rates of major cardiovascular risk factors including HbA1c, blood pressure and low-density lipoprotein cholesterol were improved among hospitalized patients in Tianjin, China.